Tunes That Bind: Paul J. Seelig, Eva Gauthier, Charles T. Griffes, and the Javanese Other - Spiller, Henry (Journal of the Society for American Music, 2009)
The powerful concept of orientalism has undergone considerable refinement since Edward Said popularized the term with his eponymous book in 1978. Orientalism typically is presented as a totalizing process that creates polar oppositions between a dominating West and a subordinate East. U.S. orientalisms, however, reflect uniquely North American approaches to identity formation that include assimilating characteristics usually associated with the Other. This article explores the complex relationship among three individuals—U.S. composer Charles T. Griffes, Canadian singer Eva Gauthier, and German-trained Dutch East Indies composer Paul J. Seelig—and how they exploited the same Javanese songs to lend legitimacy to their individual artistic projects. A comparison of Griffes's and Seelig's settings of a West Javanese tune (“Kinanti”) provides an especially clear example of how contrasting approaches manifest different orientalisms. Whereas Griffes accompanied the melody with stock orientalist gestures to express his own fascination with the exotic, Seelig used chromatic harmonies and a chorale-like texture to ground the melody in the familiar, translating rather than representing its Otherness. The tunes that bind Griffes, Gauthier, and Seelig are only the raw materials from which they created their own unique orientalisms, each with its own sense of self and its own Javanese others.
Publisher: Cambridge University Press